Incidence and predictors of mortality among low birth weight neonates in Africa: a systematic review and meta-analysis - Mengstie, Leweyehu Alemaw; Teklehaimanot, Wegayehu Zeneb; Gebeyehu, Mohammed Tesema; Abemie, Worku; Ayfokru, Abatwoy; Dessie, Yihenew Ayehu; Tefera, Mitiku; Girma, Bekahegn (Frontiers in Pediatrics, 2025)
BackgroundIn Africa, the burden of low birth weight (LBW) neonatal mortality remains substantial, yet comprehensive evidence is lacking, with varied and inconclusive findings from primary studies. This systematic review and meta-analysis aimed to assess the pooled incidence and predictors of LBW neonatal mortality in Africa.MethodsIn accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we systematically searched PubMed, EMBASE, Cochrane Library, African Journals Online, Web of Science, Google Scholar, and Google for relevant studies. The Newcastle Ottawa Scale was used to assess study quality. Heterogeneity and publication bias were evaluated using the I2 statistic and Egger's test. A random-effects model was applied due to significant heterogeneity, with pooled incidence and 95% confidence intervals (CIs) calculated. Subgroup and sensitivity analyses explored sources of heterogeneity.ResultsThis meta-analysis included 28 studies involving 56,775 LBW neonates. The pooled incidence of LBW neonatal mortality in Africa was 33.1% per 100 person-years (95% CI: 19.54–46.65), with substantial heterogeneity (I2 = 99.9%, P < 0.001). Predictors associated with LBW neonatal mortality included extremely low birth weight (PHR = 4.37, 95% CI: 2.62–7.29), lack of antenatal care follow-up (PHR = 2.84, 95% CI: 1.21–6.67), perinatal asphyxia (PHR = 1.73, 95% CI: 1.38–2.16), necrotizing enterocolitis (PHR = 2.80, 95% CI: 2.03–3.86), preterm birth (PHR = 3.17, 95% CI: 1.88–5.35), respiratory distress syndrome (PHR = 1.87, 95% CI: 1.57–2.23), sepsis (PHR = 2.04, 95% CI: 1.59–2.63), lack of kangaroo mother care (PHR = 5.29, 95% CI: 2.76–10.16), maternal diabetes mellitus (PHR = 2.74, 95% CI: 1.87–4.01), and maternal HIV infection (PHR = 4.47, 95% CI: 2.06–9.67).ConclusionsThis study highlights a concerning high incidence of LBW neonatal mortality in Africa. Strategies targeting these predictors, such as improving antenatal care, promoting kangaroo mother care, and managing maternal health conditions like diabetes and HIV, could substantially reduce LBW neonatal mortality in the region. Policymakers and healthcare providers should prioritize these interventions to mitigate the high burden of LBW neonatal mortality and improve neonatal health outcomes across Africa.Systematic Review Registrationidentifier, CRD42024560375.